x+y=4 sqrt(2*(x^2+(y-2)^2)*((x-3)^2+(y-3)^2))=x^2+(y-2)^2+(x-3)^2+(y-3)^2-10

1 уравнение:
2 уравнение:
3 уравнение:
4 уравнение:
5 уравнение:
6 уравнение:
7 уравнение:
8 уравнение:
9 уравнение:
10 уравнение:
11 уравнение:
12 уравнение:
13 уравнение:
14 уравнение:
15 уравнение:
16 уравнение:
17 уравнение:
18 уравнение:
19 уравнение:
20 уравнение:
21 уравнение:
22 уравнение:
23 уравнение:
24 уравнение:
25 уравнение:
26 уравнение:
27 уравнение:
28 уравнение:
29 уравнение:
30 уравнение:
31 уравнение:
32 уравнение:
33 уравнение:
34 уравнение:
35 уравнение:
36 уравнение:
37 уравнение:
38 уравнение:
39 уравнение:
40 уравнение:
41 уравнение:
42 уравнение:
43 уравнение:
44 уравнение:
45 уравнение:
46 уравнение:
47 уравнение:
48 уравнение:
49 уравнение:
50 уравнение:
51 уравнение:
52 уравнение:

Решение

Вы ввели
[TeX]
[pretty]
[text]
x + y = 4
$$x + y = 4$$
   _________________________________________                                           
  /   / 2          2\ /       2          2\     2          2          2          2     
\/  2*\x  + (y - 2) /*\(x - 3)  + (y - 3) /  = x  + (y - 2)  + (x - 3)  + (y - 3)  - 10
$$\sqrt{2 \left(x^{2} + \left(y - 2\right)^{2}\right) \left(\left(x - 3\right)^{2} + \left(y - 3\right)^{2}\right)} = \left(y - 3\right)^{2} + \left(x - 3\right)^{2} + x^{2} + \left(y - 2\right)^{2} - 10$$
Быстрый ответ
[TeX]
$$x_{1} = -1$$
=
$$-1$$
=
-1

$$y_{1} = 5$$
=
$$5$$
=
5
$$x_{2} = 4$$
=
$$4$$
=
4

$$y_{2} = 0$$
=
$$0$$
=
0
Численный ответ
[pretty]
[text]
x1 = 4.00000000000000
y1 = 4.808670666368384e-24
x2 = 4.00000000001093
y2 = -1.093047866993157e-11
x3 = 4.00000000000000
y3 = 0.0
x4 = -1.00000000000000
y4 = 5.00000000000000
x5 = 4.00000000000000
y5 = -2.051348822593039e-23